Perlindungan Hukum terhadap Investor dalam Kegiatan Penanaman Modal di Indonesia - Oktavian Risnaldi; Zulfikri Toguan; Alif Oemar Al Ghifari (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2026)
Legal protection for investors plays an important role in creating a stable and equitable investment climate in Indonesia. The national investment law system regulates investor protection through Law Number 25 of 2007 concerning Investment and various related regulations that provide both preventive and repressive legal safeguards. Preventive protection is reflected in the provision of legal certainty, equal treatment for investors, and simplification of licensing procedures, while repressive protection is implemented through litigation and arbitration mechanisms for resolving investment disputes. This research applies a normative legal method using statute, conceptual, and analytical approaches. Legal materials were obtained through document studies involving primary, secondary, and tertiary legal sources and were analyzed qualitatively. The findings indicate that the implementation of investor legal protection still encounters several obstacles, including inconsistent regulations, overlapping institutional authority, weak law enforcement, and inefficient investment service bureaucracy. These conditions affect the effectiveness of legal certainty and investor confidence in Indonesia’s investment sector. Strengthening regulatory harmonization, improving legal certainty, and reforming bureaucratic and dispute resolution mechanisms are therefore essential to support a more conducive and fair investment environment.